Zakončení přídavných jmen na -ózní v současné češtině - Artemov, Andrej (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2018)
The article deals with the emergence of new connotations in word formation using the suffix -ózní (-osní) for adjectival neologisms and occasionalisms. In contemporary spoken and written Czech language there are a number of such neologisms. The author bases his findings in examining the SYN2015 corpus of the Czech National Corpus and available Czech dictionaries. Besides neologisms and occasionalism, the attention is given to loans that are already used and terminological adjectives with the aforementioned suffix.
Adjectives ending in -ózní in contemporary Czech language
Keywords: adjectives; suffix -ózní (-osní); loans; terminology; neologisms; nonce words (occassionalisms); Czech language